Business Development Services (BDS) and SMME Development in South Africa - Zilwa, Portia (Graduate School of Business (GSB), 2021)
Small businesses are regarded as economic growth engines with the potential to address the unemployment crisis in South Africa. The government has limited capacity to employ the majority of the unskilled and semi-skilled who are unemployed. Agencies and private organisations offering business development services (BDS) are required to assist small, medium and micro enterprises (SMMEs) help government to address unemployment. Small and medium enterprises (SMEs) are recognised for the crucial role they play in activating and supporting economic growth. While much attention and hope has been placed on SMEs to provide the much-needed jobs, they are faced with enormous challenges and continue to fail. These challenges make it impractical for SMEs to realise their full potential and deliver to the government's and society's expectations. It is documented that SMEs face unique problems, which negatively affect their prospects and as a result, weaken their capacity to contribute to sustainable economic growth. Government and other private sector stakeholders have availed various types of business support in South Africa both as financial and non-financial support to assist SMEs overcome these problems. There has also been an emergence of business development service providers (BDSPs) that seek to extend support to SMEs, to ensure their sustainability, improve production techniques, market access and increase competitiveness but this has not yielded the desired results. Business development services refer to services that improve the performance of the enterprise, its access to markets, and its ability to compete. This study sought to explore the nature of BDS offered to SMMEs with a view to help them remain sustainable. Further, the study explored the challenges faced by BDSP. The study used an inductive qualitative research approach and employed semi-structured interviews to collect data. The population of the study consisted of SME business development service providers in South Africa, with an eventual study sample size comprised of ten providers. The findings indicate that there is a range of services offered to SMEs, with training and technical assistance and market access being the focus areas. While providers offer these services to SMEs, they themselves experience various challenges such as internal challenges which include funding and resources; expertise and skills levels of providers; and design of services. In addition, there are external challenges such as payment inability of SMMEs; low market awareness; commitment to and from SMMEs; perceived value of BDS; finding the right clients; and the business operating environment, which hinder their service provision. iii The study concludes by providing recommendations on approaches that BDS providers can adopt to offer solutions to some of the identified challenges. These approaches include: developing sector-specific approaches in delivering business development service; attracting enterprise and supplier development funds as a possible strategy to solve the lack of resources in this sector; alignment of the Broad-Based Black Economic legislative framework to business development services strategies; introduction of professional standards and guidelines in the business development services sector and implementation of an impact assessment matrix.